How much are fathers asked to contribute when children live with low-income mothers? New evidence from Colombia, Finland, Peru, Uruguay, and the United States - Cuesta, Laura; Bucheli, Marisa; Meyer, Daniel R.; Hakovirta, Mia (Cambridge University Press (CUP), 2026)
This article provides new exploratory information on child support amounts expected for non-resident fathers of children living with low-income, unemployed mothers in Colombia, Finland, Peru, the United States, and Uruguay. Using vignette data obtained through extensive interviews with judicial and social service personnel and child support experts, we investigated whether child support is expected and its amount when single mothers are unemployed, considering four different levels of earnings for fathers. In all countries but Finland, child support is expected when the father has only temporary employment. For the lowest income fathers, child support expectations in Colombia, Peru, and Uruguay are similar or higher than the United States and higher in Finland. In all countries except Colombia, child support expectations are higher when father's income is higher. We discuss implications for policy and future research.